Dampak Pembebasan Lahan Pasar Tradisional terhadap Proses Sosial Masyarakat di Kota Banjarmasin - Sierna, Yovana Mega; Damaiyanti, Varinia Pura (Huma: Jurnal Sosiologi, 2025)
The Old Market in Banjarmasin City is a traditional trading hub with significant historical, economic, and social value for the local community. However, the planned land acquisition in the Pasar Batuah area presents serious challenges for economic actors and residents who rely on the market for their livelihoods. This study aims to evaluate the social impacts of the land acquisition and analyze the roles and dynamics of the actors involved in the process. A qualitative descriptive approach was used, with data collected through field observations, interviews with traders, affected residents, government officials, and documentation from media and archives. The findings reveal that land acquisition produces dual impacts: on one hand, it offers opportunities for urban spatial planning and infrastructure development; on the other, it leads to economic uncertainty, loss of livelihoods, and social fragmentation, particularly due to inherited land disputes. Divergent perceptions between the government and the community contribute to tensions that affect the relocation process. Unanticipated impacts also emerged, such as increased vulnerability among marginalized groups and the erosion of community bonds within the market. Key actors, including local government, community leaders, NGOs, and the media, play a significant role in shaping & policy direction and public response. These findings highlight the need for participatory approaches in land acquisition projects to ensure that development does not compromise social sustainability. Further research should explore the socio-economic dimensions of land acquisition in traditional markets, the role of cultural identity in sustaining market communities, and inclusive policy strategies that protect the rights of affected populations.